Peran Gigi pada Tumbuh Kembang Dentofasial (Laporan Kasus) - Retno Hayati (Faculty of Dentistry, Universitas Indonesia, 2015)
The function of dentition is not only for mastication, the other function is to coordinate the growth of maxilla, midface and mandible. This important function was done through occlusal contact during occlusion. The occlusal surfaces become a link of stomato-gnathic system. This case report showed the midface growth was affected by agenesis. The first case was 10-years old girl with congenital missing 16 and 26. The relationship of upper and lower arch erior was edge to edge and crossbite. In posterior, the occlusal contact were found between upper second primary molars and lower first permanent molars. The second and third cases were 5 and 9-years old boys. They were siblings with ectodermal dysplasias and partial anodontia. The facial profile of these children were concave. The relationship of maxilla and mandible was class III. The manifestation of growth retardation was shown by cephalometric measurement, SN, Ans-Pns, Ptm-A, N-Me, Ans-Me, S-Go were smaller than standard normal children.